2018
DOI: 10.17509/image.v7i2.23135
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Debt to Equity Ratio, Earning Per Share, Return on Assets Dan Price Earning Ratio Terhadap Harga Saham

Abstract: Penelitian ini bertujuan untuk menganalisis pengaruh Debt to Equity Ratio (DER), Earning Per Share (EPS), Return on Assets (ROA) terhadap Harga Saham dengan Price Earning Ratio (PER) sebagai Variabel Intervening. Penelitian ini menggunakan metode kuantitatif. Jenis data sekunder bersumber dari laporan keuangan Bursa Efek Indonesia yang telah dipublikasikan. Analisis data menggunakan analisis jalur (path analysis).Hasil penelitian menunjukkan: (1) Debt to Equity Ratio tidak berpengaruh signifikan terhadap Price… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Apart from that, this research also indicates that a high price-earnings ratio does not mean the company has good performance for investment. The results of this research are in line with previous research, namely, which states that the price-earnings ratio does not influence stock prices (Dewi & Utiyati, 2017;Fajrian & Sumawidjaja, 2018;Suharti & Tannia, 2020).…”
Section: The Influence Of Price Earning Ratio (Per) On Stock Pricessupporting
confidence: 91%
See 1 more Smart Citation
“…Apart from that, this research also indicates that a high price-earnings ratio does not mean the company has good performance for investment. The results of this research are in line with previous research, namely, which states that the price-earnings ratio does not influence stock prices (Dewi & Utiyati, 2017;Fajrian & Sumawidjaja, 2018;Suharti & Tannia, 2020).…”
Section: The Influence Of Price Earning Ratio (Per) On Stock Pricessupporting
confidence: 91%
“…According to research (Beliani & Budiantara, 2017;Ratih et al, 2016) found that the Price Earning Ratio has a positive effect on stock prices. However, different research conducted by Fajrian & Sumawidjaja (2018); Suharti & Tannia (2020); Dewi & Utiyati (2017) ound that the Price Earning Ratio did not affect stock prices.…”
Section: Introductionmentioning
confidence: 93%
“…the company's stock price, thereby encouraging investor interest to invest (Indriawati & Nurfadillah, 2020). The results of empirical studies prove that Earning per Share (EPS) has an influence on stock prices, such as empirical studies (Marcellyna & Hartini, 2011); (Choirani, 2013); (Muksal, 2015); (Yumia & Khairunnisa, 2015); (Wicaksono, 2015); (Saryanti, 2015); (Mujiono, 2017); (Fajrian & Sumawidjaja, 2018); (Lilianti, 2018); (Azmy, Ahmad;Lestari, 2019); (Alifiawan et al, 2019); and (Indriawati & Nurfadillah, 2020). However, there are also contradictory findings that Earning per Share (EPS) does not have an effect on stock prices, such as empirical studies (Aning Tyas & Septa Saputra, 2016); (Sumaryanti, 2017); and (Andry, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to research conducted by Kundiman (2016) and Sari (2021), Return On Assets (ROA) has a significant effect on stock prices. However, contrary to Fajrian & Sumawidjaja (2018) and Wicaksono & Sari (2019), Return On Assets (ROA) does not have a significant effect on stock prices. The Leverage Ratio functions to measure the amount of company assets financed by debt.…”
Section: Introductionmentioning
confidence: 76%